Poly[[μ(2)-aqua-aqua(μ(3)-3,5-dinitrosalicylato)barium(II)] monohydrate] - Song, Wen-Dong (International Union of Crystallography, 2008)
In the title coordination polymer, {[Ba(C(7)H(2)N(2)O(7))(H(2)O)(2)]·H(2)O}(n), the Ba(II) atom is ten-coordinated by seven O atoms from four 3,5-dinitrosalicylatate ligands, two μ(2)-bridging aqua ligands and one water molecule. The coordination mode is best described as a bicapped square-antiprismatic geometry. The 3,5-dinitrosalicylatate ligands bridge three Ba atoms. Centrosymmetrically related dinuclear barium units, with a Ba⋯Ba separation of 4.767 (5) Å, form infinite chains, which are further self-assembled into a supramolecular network through intermolecular O—H⋯O hydrogen-bonding interactions between O atoms of 3,5-dinitrosalicylatate ligands and water molecules.